Caregivers’ Sensemaking of Children’s Hereditary Angioedema: A Semiotic Narrative Analysis of the Sense of Grip on the Disease - Freda, Maria Francesca; Savarese, Livia; Dolce, Pasquale; Picione, Raffaele De Luca (Frontiers in Psychology, 2019)
Background and aims. In pediatrics receiving a diagnosis of a chronic condition is a matter that involves caregivers at first. Beyond the basic issues of caring for the physical body of the ill child, caregivers’ manners of facing and making sense of the disease orient and co-construct their children’s sensemaking processes of the disease itself. The aim of this article is to explore the experience of a rare chronic illness, Hereditary Angioedema (HAE), in pediatrics, from the caregivers’ perspective. Hereditary Angioedema is characterized by subcutaneous swellings that can involve the mucosal tissues of external as well as internal parts of the body, manifesting in a highly variable and unpredictable way in terms of localization, severity, and frequency. Materials and methods. Within a qualitatively-driven research design, we conducted a qualitative narrative semiotic analysis of n.28 mothers’ narratives on their children’s disease experience. Narratives were collected by an ad hoc interview on three domains of the disease experience: A. interpretation of the disease variability; B. dialogical processes; C. management of the disease. Subsequently, we executed a TwoStep cluster analysis for categorical data to detect cross-sectional profiles of the maternal sensemaking processes of the disease. Results. The coding grid was built analyzing the characteristic of the narrative links that orient the connection between the elements of the experience within each domain: A. the connection among events, for the domain of the interpretation of the disease variability; B. the connection between self and other, for the domain of the dialogue; C. the connection among sensemaking and actions, for the domain of the management of the disease. Results from cluster analysis show three narrative profiles: 1. adempitive; 2. reactive; 3. dynamic. Discussion. Profiles will be discussed in the light of the general conceptual framework of the Sense of Grip on the Disease (SoGoD) highlighting the importance of those sensemaking processes which, instead of relying on a coherent and close interpretation of the disease, are characterized by a degree of tolerance for the uncertainty and the unknowingly.